Istri Sebagai Pelaku Kekerasan Fisik Terhadap Suami Dalam Rumah Tangga - Jaqualine Monicha Talahatu; Margie Gladies Sopacua; Erwin Ubwarin (PATTIMURA Law Study Review, 2023)
ABSTRACT: Domestic violence is violence perpetrated by a husband against his wife, but the victims are mainly women as wives. Domestic violence is any violence based on gender differences that causes pain or suffering, especially for women as wives, including threats, coercion, restrictions on freedom both in public and at home. However, the reality is that domestic violence also occurs against husbands committed by wives. One of the cases of physical violence committed by a wife against her husband is criminal case number LP-B/486/XI/2022/Maluku, in which the wife actually committed the crime of physical violence against her husband. This study uses normative legal research methods. Peter Mahmud Marzuki, argues that normative legal research which is another name for doctrinal legal research is also known as library research or document study because this research is carried out or shown only on written regulations or other legal materials. The causes of physical violence against husbands are; 1) Domination factor where the wife is more dominant than the husband, this is seen as the case that the wife feels that her job as a civil servant or other job has a greater source of income than the husband; 2) Psychic Factors where when the husband comes home drunk, gambling, not supporting the wife and children in the household, then the wife reprimands repeatedly but these things are still being done by the husband; 3) Economic Factors; economic conditions that are classified as middle or sufficient with the increasing needs of life will become a problem for the wife against the husband 4) Infidelity Factors; Infidelity factor; infidelity committed by the wife brings consequences and causes domestic disputes and ultimately leads to domestic violence 5) Fatigue Factor; excessive work demands are also where a person feels emotional pressure or what is commonly called emotional fatigue, thus causing domestic violence 6) Environmental Factors where the environment is a place to live for people who are very sensitive to negative environmental influences; and 7) The Liquor Factor where alcoholic beverages can make the person lose self-control and if consumed excessively, it results in drunkenness so as to commit negative actions such as violence.